Positive selection differs between protein secondary structure elements in Drosophila. - Ridout, K; Dixon, C; Filatov, D (2010)
Different protein secondary structure elements have different physicochemical properties and roles in the protein, which may determine their evolutionary flexibility. However, it is not clear to what extent protein structure affects the way Darwinian selection acts at the amino acid level. Using phylogeny-based likelihood tests for positive selection, we have examined the relationship between protein secondary structure and selection across six species of Drosophila. We find that amino acids that form disordered regions, such as random coils, are far more likely to be under positive selection than expected from their proportion in the proteins, and residues in helices and beta-structures are subject to less positive selection than predicted. In addition, it appears that sites undergoing positive selection are more likely than expected to occur close to one another in the protein sequence. Finally, on a genome-wide scale, we have determined that positively selected sites are found more frequently toward the gene ends. Our results demonstrate that protein structures with a greater degree of organization and strong hydrophobicity, represented here as helices and beta-structures, are less tolerant to molecular adaptation than disordered, hydrophilic regions, across a diverse set of proteins.